The Analysis of Affiliate Marketing, Video Marketing, and Halal Brand Awareness Factor in Influencing Consumer Decisions in Purchasing Implora Products - Tussifah, Hamidah; Nabila, Adzimatinoor Nabila (Indonesian Journal of Economics and Management, 2024)
Effective marketing strategies are crucial with the rapid growth of e-commerce and fierce competition in the cosmetics industry. This study analyzes the impact of affiliate marketing, video marketing, and halal brand awareness on consumer purchase decisions for Implora products. Using a quantitative approach, data were collected through questionnaires, observations, and surveys from 122 respondents who use Implora products, and analyzed with SPSS version 25. Multiple linear regression and T-tests reveal that affiliate marketing positively and significantly influences purchase decisions (tcount 2.497 > ttable 1.980). Conversely, video marketing shows a negative and significant effect (tcount -2.677 > ttable 1.980). Halal brand awareness positively and significantly affects decisions (tcount 3.381 > ttable 1.980), reflecting its importance in Indonesia's Muslim-majority market. Aspects like halal knowledge, hygiene, and safety enhance consumer trust, offering insights for more effective strategies to boost Implora's competitiveness and market share.